Fatigue life of E-glass fibre/zirconia/epoxy hybrid composites - Srivastava V.K. (My University, 2025)
An ultrasonic technique has been used to evaluate the degradated fatigue life of glass fibre/zirconia hybrid composites in different concentrations of sodium chloride and sulphuric acid. Results indicate that reduction in fatigue life of hybrid composites increases with increase in ultrasonic attenuation. Ultrasonic attenuation can be used to predict the fatigue life of hybrid composites before and after service. © 1988 Indian Academy of Sciences.